(untitled) (Eurasian Research Bulletin, 2023)
Present article is devoted to the peculiarities of the structure and function, morphometric parameters of the basic structures of the central and peripheral organs of the immune system. It reveals the patterns of the development of these organs at different stages of postnatal ontogenesis. The data of the domestic and foreign literature on the impact of environmental factors on the structural changes in the thymus and spleen on the organ, tissue and cellular levels was analyzed. Further study of the morphological and functional organization of organs of the immune system will allow to identify and analyze the patterns of their structural and functional changes influenced by the factors of different origin.